Impact of the Resources Gap on the Interest Margin in the Jordanian Commercial Banks(1990-2011) (Global Journal of Management and Business Research, 2014)
This study aims to analyze the impact of the resources gap on the interest margin in the Jordanian Commercial Banks. Since the interest margin is the main source of profit in commercial banks, the existence of a gap have a negative impact on the interest margin. In addition, as the change in sensitive assets to interest rate and sensitive liabilities of interest rate has an impact on the bank's profits; especially when the commercial banks pay the costs of some sources of funds to increase what they get from the benefits derived from credit facilities of credit interest and the debt interest. This is all embarked upon within a sample that included eight Jordanian commercial banks (out of thirteen are banks in Jordan)..The analysis relies on the annual data for banks to identify the resource gap in the Jordanian commercial banks, their
Keywords: gap; interest margin; commercial banks